Modeling Power IoT Terminal Entity Based on OOPN. Issue 1 (1st January 2022) - Miao, Weiwei; Wei, Lei; Zeng, Zeng
Abstract: With the continuous development and ceaselessly construction of power IoT system, a huge number of power terminal entities are connected to the power IoT system, which largely affect the performance of power IoT system. The lifecycle process analysis of power IoT terminal entity becomes more and more important. However, the traditional analysis methods often have some shortcomings such as complex process and huge workload. Therefore, it is urgently needed to find out some more effective method to analyze the state and behaviour of power IoT terminal entity. To overcome the shortcomings of traditional analysis methods, an OOPN-based power IoT terminal entity model is proposed by combining object-oriented idea with Petri net technology. The proposed model has the advantages of modularity design, object-oriented, simplified calculation and great flexibility, which is verified with a case study by selecting a transformer as an example of power IoT terminal entity and comparing the data.